The spatial complexity in describing leg surfaces of Hymenoptera (Insecta), the problem and a proposed solution - Aguiar, Alexandre P.; Gibson, Gary A. P. (Zootaxa, 2010)
A significant procedural problem in describing the leg surfaces of Hymenoptera, which has not been explicitly treated in the literature before, is identified and a mitigating solution is proposed. The first accurate, three-dimensional illustrations of the surfaces of the three pairs of legs are also provided to illustrate the problem and the proposed solution. In Hymenoptera, the orientation of the front, middle and hind pairs of legs relative to the body can and often do differ in direction by up to 180º between the front and hind legs. Furthermore, the tibiae and tarsi are usually held at an abrupt angle relative to the femora. Because of this, the terms anterior, posterior, lateral, outer, mesal, inner, dorsal, and ventral, when applied to surfaces of different parts of different legs will frequently refer to non-homologous areas depending on whether the terms are interpreted or used in an anatomic sense or based on the specific direction and orientation of the part of the leg being described (vernacular sense). Authors often use the vernacular interpretation, but we show that such usage makes the terminology on average 53.1% incompatible for the same anatomical surfaces of the femora, tibiae and tarsi of the three sets of legs. To create equivalence between anatomical and vernacular senses, four intuitive vernacular terms are proposed as explanatory or auxiliary terms for the anatomical terms “dorsal”, “ventral” “anterior”, and “posterior”, respectively, kickface, gripface, foreface, and backface. The terms are proposed as auxiliary or explanatory terms and not as substitutes for the anatomical terms.